Avaliando a eficiência das distribuidoras no setor elétrico brasileiro - Mário Jorge Mendonça; Amaro Olimpio Pereira Júnior; Luis Alberto Toscano Medrano (Instituto de Pesquisa Econômica Aplicada (IPEA), 2020)
– The objective of the this study is to present an alternative approach to the current methodology implemented by Aneel for estimating efficiency of the distribution sector of electric energy in Brazil. For this purpose, Bayesian inference is applied in order to estimate a stochastic cost frontier capable of contemplating the temporal dynamics of efficiency. The consideration of this point is fundamental because the studies carried out to evaluate the efficiency of the electricity sector have neglected that part of the efficiency of a utility comes from the gain of scale due to the expansion of the market, a process that happens over time. Our sample is composed of panel data of 61 electric power concessionaires between 2003 and 2016.
Keywords: Q40; Q48; Q49; 330; electric sector; tariff revision; efficiency; stochastic frontier; Bayesian inference